2012
DOI: 10.1016/j.gloplacha.2012.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Did massive glacial dewatering modify sedimentary structures on the Amundsen Sea Embayment shelf, West Antarctica?

Abstract: Multichannel seismic reflection lines collected in the western Amundsen Sea Embayment (ASE) provide an insight into the sedimentary cover on the shelf, which documents glacial processes. Numerous columnar, reflection-poor structures penetrating the sedimentary sequences on the middle shelf form the focus of this study. The features range between 50 and 500 m in width, and from a few metres up to 500 m in height. The columns originate and end at different depths, but do not seem to penetrate to the seafloor. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…1). Oceanward dipping mid-shelf strata north of outcropping basement are observed in seismic data from the Dotson-Getz Trough collected in 1999 and 2006 (Wellner et al, 2001;Graham et al, 2009;Weigelt et al, 2009Weigelt et al, , 2012 and exhibit alternating sequences of low and high reflectivity, which Weigelt et al (2009) interpret as episodes of major glacial advances and retreat in the Miocene.…”
Section: Tectonic and Depositional Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…1). Oceanward dipping mid-shelf strata north of outcropping basement are observed in seismic data from the Dotson-Getz Trough collected in 1999 and 2006 (Wellner et al, 2001;Graham et al, 2009;Weigelt et al, 2009Weigelt et al, , 2012 and exhibit alternating sequences of low and high reflectivity, which Weigelt et al (2009) interpret as episodes of major glacial advances and retreat in the Miocene.…”
Section: Tectonic and Depositional Settingmentioning
confidence: 99%
“…Wellner et al (2001), Anderson (2002, 2003) and Dowdeswell et al (2006) described SCS datasets collected along Pine Island Trough and the Dotson-Getz Trough during RV Nathaniel B. Palmer cruise NBP9902 in 1999. More SCS data were collected on the outer shelf and the middle shelf of the western ASE during RRS James Clark Ross cruise JR141 in early 2006 Graham et al, 2009), followed by MCS data recorded on RV Polarstern cruise ANT-XXIII/4 in the same season of 2006 (Gohl, 2007;Uenzelmann-Neben et al, 2007;Weigelt et al, 2009Weigelt et al, , 2012. Due to unusually favorable sea-ice conditions in the season of early 2010, we were able to acquire more than 3500 km of MCS data from the middle to outer shelf, the slope and the continental rise of the Amundsen Sea during RV Polarstern expedition ANT-XXVI/3 (Gohl, 2010).…”
Section: Data Acquisition and Processingmentioning
confidence: 99%
“…Intraplate volcanism at 65-56 Ma led to the formation of the Marie Byrd Seamounts (Kipf et al, 2013). The crystalline basement is covered by up to 4 km of sedimentary strata, which have been extensively reworked by oceanic currents in the deep sea (Yamaguchi et al, 1988;Nitsche et al, 2000;Uenzelmann-Neben and Gohl, 2012) and by advance-retreat cycles of the ice sheet on the shelf (Lowe and Anderson, 2002;Dowdeswell et al, 2006;Nitsche et al, 2007;Uenzelmann-Neben et al, 2007;Graham et al, 2009;Weigelt et al, 2009;Weigelt et al, 2012;Gohl et al, 2013;Hochmuth and Gohl, 2013).…”
Section: Palaeoenvironmental Settingmentioning
confidence: 99%
“…Geletti and Busetti (2011) related seismic chimneys to the presence of gas hydrates, whose presence they interpreted from Bottom-Simulating Reflectors (BSR) in their seismic records in the Ross Sea. In contrast, Weigelt et al (2012) suggested that the reflection-poor vertical pipe-like structures in sedimentary sequences on the middle shelf of the Amundsen Sea Embayment represent mud-diapirs rising from water-rich sediments, and suggested that their formation has been strongly influenced by glacial/interglacial cycles.…”
Section: Indications Of Potential Ventingmentioning
confidence: 99%
“…the Vøring and Møre margin basins, or the Ulleung Bain (Planke et al 2005;Horozal et al 2009). Around Antarctica, seismic chimneys have also been observed in basins of the Amundsen Sea and Ross Sea Embayment (Geletti and Busetti 2011;Weigelt et al 2012). Geletti and Busetti (2011) related seismic chimneys to the presence of gas hydrates, whose presence they interpreted from Bottom-Simulating Reflectors (BSR) in their seismic records in the Ross Sea.…”
Section: Indications Of Potential Ventingmentioning
confidence: 99%